Optimization of Papaya (Carica papaya L.) Leaf Extract Emulgel Formulation using Simplex Lattice Design for Topical Application - Nurfiana Rachmawati; Siti Aisiyah; Mega Novita; Dian Marlina (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Papaya (Carica papaya L.) leaf extract is rich in bioactive compounds with antioxidant, anti-inflammatory, and wound healing effects, making it a promising candidate for topical applications. However, there are challenges in formulating an effective and stable system. This study aimed to optimize the formulation of Papaya leaf extract emulgel using the simolex lattice design (SLD) method with various concentrations of Carbopol 940, Olive oil, and Tween 80. Eight formulations were evaluated for pH, viscosity, spreadability, and physical stability. This study showed that the optimal formulation of 1.0% Carbopol 940, 15% olive oil, and 10% Tween 80, which produced an emulgel with pH 6.1, viscosity of 4.580 cP, and spreadability of 6.8 cm, which are acceptable according to pharmaceutical standards. The above formulation showed good physical stability over 28 days of storage. In conclusion, the SLD method can be applied to developing typical herbal-based products and standardized for better effectiveness and stability.